2020
DOI: 10.3389/fphar.2020.00539
|View full text |Cite
|
Sign up to set email alerts
|

Shape Matters: Comprehensive Analysis of Star-Shaped Lipid Nanoparticles

Abstract: The research of lipid nanoparticles (LNPs) has been ongoing for more than three decades, and more research are still being carried out today. Being the first Food and Drug Administration (FDA)-approved nanomedicine, LNPs not only provide various advantages, but also display some unique properties. The unique lipid bilayer structure of LNPs allows it to encapsulate both fat-soluble and water-soluble molecules, hence enabling a wide range of possibilities for the delivery of therapeutic agents with different phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Today, a number of works are devoted to the synthesis of different shaped SLN [ 20 , 43 , 44 , 45 , 46 ]. It has been shown that the shape of SLN can change depending on the nature and size of the substituents in the molecule [ 20 , 46 ], the interaction of the solute with the solvent [ 43 ], and the loading of SLN with some substance [ 45 ]. In this work, we studied the influence of substituent nature in the structure of monosubstituted pillar[5]arenes on the size and stability of formed particles.…”
Section: Resultsmentioning
confidence: 99%
“…Today, a number of works are devoted to the synthesis of different shaped SLN [ 20 , 43 , 44 , 45 , 46 ]. It has been shown that the shape of SLN can change depending on the nature and size of the substituents in the molecule [ 20 , 46 ], the interaction of the solute with the solvent [ 43 ], and the loading of SLN with some substance [ 45 ]. In this work, we studied the influence of substituent nature in the structure of monosubstituted pillar[5]arenes on the size and stability of formed particles.…”
Section: Resultsmentioning
confidence: 99%
“…The shape of the particles has likewise been shown to impact tumor uptake following i.v. administration, with star-shaped particles showing a higher uptake in tumors . However, what we understand of the EPR effect and passive tumor targeting is undergoing a radical shift with a growing body of evidence suggesting that a particulate nature alone is unsuitable for tumor targeting in the clinic .…”
Section: Resultsmentioning
confidence: 99%
“…Lipid nanoparticles have been used as an alternative TDDS for pharmaceutical drugs and cosmetic compounds since the early 1990s [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. A solid lipid nanoparticle (SLN) was prepared by the exchange of the liquid lipid oil of the emulsions by solid lipid, which remains at a solid-state at room temperature and body temperature [ 66 , 67 ].…”
Section: Transdermal Drug Delivery Using Nanocarriermentioning
confidence: 99%
“…The SLNs are useful for incorporating lipophilic, hydrophilic, and water-insoluble compounds owing to their structural characteristics. Nanostructured lipid carriers (NLC) are known as the second generation of lipid nanoparticles [ 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ]. A variety of amphiphilic molecules can be used to prepare NLC ranging from phospholipids to artificial surfactants.…”
Section: Transdermal Drug Delivery Using Nanocarriermentioning
confidence: 99%
See 1 more Smart Citation